2021
DOI: 10.3389/fbloc.2021.720454
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Readiness: Blockchain Adoption is Driven Externally

Abstract: Blockchain technology has been extensively tested, implemented, used, or even abandoned by organizations. Whether organizations adopt blockchain technology depends on many factors. Previous literature has identified a range of potential factors affecting the adoption of blockchain technology, but most studies have focused solely on a subset of specific factors. As a result, these studies can provide only limited explanations for the varying degrees of blockchain adoption. By relying on the well-established Tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 69 publications
1
13
0
2
Order By: Relevance
“…First, the highest DANP influential crite-rion is C4, which suggests that the top management support would be the most critical driving force for a bank to embrace an innovative Fintech strategy. This result echoes a previous work [43] and emphasizes a crucial factor overlooked in the previous study [26], based on the Technological Acceptance Model (TAM). On the other side, technol-ogy-related issues are not the primary concerns.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, the highest DANP influential crite-rion is C4, which suggests that the top management support would be the most critical driving force for a bank to embrace an innovative Fintech strategy. This result echoes a previous work [43] and emphasizes a crucial factor overlooked in the previous study [26], based on the Technological Acceptance Model (TAM). On the other side, technol-ogy-related issues are not the primary concerns.…”
Section: Discussionsupporting
confidence: 90%
“…Support from the top management of banks is crucial to adopting new technologies. Several studies highlight its critical importance in diverse industries [40][41][42][43]. Our interviews with domain experts found that high-level management support often influences banks to consider new technologies.…”
Section: Organization and Operation Managementmentioning
confidence: 90%
“…Although DOI theory encompasses both TOE and the TAM factors, it is limited, because it does not emphasise external factors (Oliveira & Martins 2011). Blockchain Adoption Model addresses, to some extent, the external factors, which are categorised as ecosystem factors, but fails to consider industry and country-specific issues Lustenberger et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused strongly on the factors influencing the adoption of blockchain by discussing the technical characteristics of blockchain technology, such as open access, decentralised consensus, immutability and distributed verification. Furthermore, studies attempted to show how the adoption of blockchain may lead to more transparency, efficiency and disintermediation when applied to various industries (Lustenberger, Malešević & Spychiger 2021). Researchers have applied traditional technology frameworks and theories to the adoption of blockchain technology.…”
Section: Introductionmentioning
confidence: 99%
“…It enables a number of geographically scattered network members to guarantee the authenticity and accuracy of all financial dealings. There have been many different consensus algorithms created by academics since the advent of BC and distributed ledger technologies, each catering to the needs of the user (Lustenberger et al, 2021;Sun et al, 2018). The implementation of BC into the operations of both small and large-scale firms may increase security, privacy, and data transparency; however, few studies have explored the potential influence of BC on organizations (Joshi et al, 2022).…”
Section: Blockchainmentioning
confidence: 99%